2022
DOI: 10.1186/s13756-022-01138-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collaborative physician-pharmacist stewardship strategies on prophylactic antibiotic practices: a quasi-experimental study

Abstract: Background An effective use of surgical antibiotic prophylaxis (SAP) appears essential to prevent the development of infections linked to surgery while inappropriate and excessive prescriptions of prophylactic antibiotics increase the risk of adverse effects, bacterial resistance and Clostridium difficile infections. In this study, we aimed to analyze SAP practices in an acute secondary hospital in Belgium during the years 2016–2021 in order to evaluate the impacts of combined stewardship inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The current waiting time for a routine consultation at the HKWC specialist outpatient clinic is currently in excess of 8 years. Experience from other countries has shown that selected patients with suspected penicillin allergy can be delabeled successfully by clinicians who are not trained in allergy (i.e., nonallergists) ( 13 16 ). A multidisciplinary effort with nonallergists would, therefore, be extremely invaluable to overcome the magnitude of penicillin allergy labels.…”
Section: Introductionmentioning
confidence: 99%
“…The current waiting time for a routine consultation at the HKWC specialist outpatient clinic is currently in excess of 8 years. Experience from other countries has shown that selected patients with suspected penicillin allergy can be delabeled successfully by clinicians who are not trained in allergy (i.e., nonallergists) ( 13 16 ). A multidisciplinary effort with nonallergists would, therefore, be extremely invaluable to overcome the magnitude of penicillin allergy labels.…”
Section: Introductionmentioning
confidence: 99%